Determination of k-factors of HVAC system components using measurement and CFD modelling - Smith, Shaun J. (1998)
This thesis conforms conventional and advanced experimental techniques for the measurement of and mathematical prediction of velocity pressure-loss factors (kfactors) for fittings used in heating, ventilation and air-conditioning (HVAC) systems. After an extensive study of different tracer-gas experimental techniques, the constant injection method is applied to various duct fittings on a small scale HVAC system situated in a laboratory. The results are compared with those of experiments performed using a more conventional technique using a Pitot-static tube. The basis of the experimental procedure is to achieve an accurate method of measuring the mean air velocity within a duct. This allows an accurate estimate of the velocity pressure-lossf actor to be obtained.